2023
DOI: 10.3390/su15043105
|View full text |Cite
|
Sign up to set email alerts
|

A Research Paradigm for Industrial Spatial Layout Optimization and High-Quality Development in The Context of Carbon Peaking

Abstract: The reasonable spatial layout of industries is crucial to carbon reduction and high-quality economic development. This paper establishes a research paradigm for optimizing the industrial spatial layout and high-quality development in the context of carbon peaking. Based on the perspectives of industrial transfer, the static agglomeration index, dynamic agglomeration index, industrial gradient coefficient, and low-carbon competitiveness index are used to analyze industrial agglomeration, competition status, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Carbon sink capacity is a significant endogenous driving force of carbon sequestration. The distribution pattern of carbon is influenced by land-use and land-cover change, and structural and environmental factors [23,24]. Improving carbon sink capacity requires a holistic approach that considers multiple land types.…”
Section: System Construction Of Carbon Sink Capacity and High-quality...mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon sink capacity is a significant endogenous driving force of carbon sequestration. The distribution pattern of carbon is influenced by land-use and land-cover change, and structural and environmental factors [23,24]. Improving carbon sink capacity requires a holistic approach that considers multiple land types.…”
Section: System Construction Of Carbon Sink Capacity and High-quality...mentioning
confidence: 99%
“…These studies have enriched the research content of the evaluation index system. Some recent studies [23][24][25] have explored the relationship between carbon sequestration and economic growth, while others have constructed an indicator system based on the ecological niche theory to measure and analyze the ecological niche for high-quality development in resource-based cities. However, the coupling relationship between high-quality economic development and ecological carbon sinks has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…The report of the 20th National Congress of the Communist Party of China pointed out that highquality development is the primary task of comprehensively building a modern socialist society [1]. Therefore, in recent years, the central task of the development of university education has been to achieve high-quality development, and the high-quality development of finance is an important and powerful support for the high-quality development of university education [2]. With the continuous development of universities, finance has become increasingly crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that optimizing the industrial layout and adjusting the industrial structure are the fundamental ways of transforming the economic development mode [ [ 3 , 4 ]]. Promoting green upgrading and layout optimization of industries and achieving the green and sustainable development of the economy have also become the frontiers of cross-disciplinary research in geography and economics.…”
Section: Introductionmentioning
confidence: 99%